PENGARUH SERTIFIKASI GURU DALAM JABATAN MELALUI PENILAIAN PORTOFOLIO TERHADAP KINERJA GURU BERSERTIFIKAT DI SMA NEGERI KABUPATEN MAGELANG (KOMPENSASI SEBAGAI VARIABLE INTERVENING) - P a r t o n o, P a r t o n o; Nurmawati, Ira (Dinamika Pendidikan, 2010)
Professional teachers are teachers who have passed the certification. The problem of this study is how much the influence of a teacher certification directly and indirectly as well as the influence of compensation on the performance of certified teachers in State High Schools in Magelang Regency. The objective of this study is to analyze the direct and indirect influences of teacher certification and compensation for the certified teachersâ performanceÂ  in High Schools in Magelang Regency. Population and sample were 85 certified teachers from 10 High Schools in Magelang District. Data was collected by questionnaire and documentation, whereas data analysis techniques was path analysis. From the research,Â  There is significant relationship between teacher certification in office through portfolio assessment of teacher performance SMA certified as Magelang regency, either directly or indirectly through compensation as an intervening variable. Suggestions in this study as follows (1) Teachers need to provide enrichment for students who excel. In addition, teachers also have to increase their creativity in providing activities to the achievement of students who have below average grade. (2) For further research, is expected to develop this research. With the review of certifications and other factors that may affect the performance of teachers.